Improving Outcomes and Preventing Complications in Cranial Base Surgery - Nicola Montano; Renata Martinelli; Joao Paulo Almeida (Brain Sciences)
Skull base surgery has evolved remarkably since the pioneering techniques of early 20th-century surgeons, such as Schloffer and Cushing, who laid the foundation for transcranial and transnasal approaches [...]